An improved slant path attenuation prediction method in tropical climates - Abdulrahman, A Y; Tharek, Abdul Rahman; Islam, Md Rafiqul; Olufeagba, B J; Yussuff, A; Khamis, N H (The Radioengineering Society, 2013)
An improved method for predicting slant path attenuation in tropical climates is presented in this paper. The proposed approach is based on rain intensity data R0.01 (mm/h) from 37 tropical and equatorial stations; and is validated by using the measurement data from a few localities in tropical climates. The new method seems to accurately predict the slant path attenuation in tropical localities, and the comparative tests seem to show significant improvement in terms of the RMS of the relative error variable compared to the RMS obtained with the SAM, Crane, and ITU-R prediction models.